Transcriptional Repression of Ferritin Light Chain Increases Ferroptosis Sensitivity in Lung Adenocarcinoma - Wang, Yikun; Qiu, Shiyu; Wang, Hong; Cui, Jiangtao; Tian, Xiaoting; Miao, Yayou; Zhang, Congcong; Cao, Leiqun; Ma, Lifang; Xu, Xin; Qiao, Yongxia; Zhang, Xiao (Frontiers in Cell and Developmental Biology, 2021)
Ferroptosis is an iron- and lipid peroxidation-dependent form of regulated cell death. Release of labile iron is one of the important factors to affect the sensitivity to ferroptosis. Yes-associated protein (YAP) controls intracellular iron levels by affecting the transcription of ferritin heavy chain (FTH) and transferrin receptor (TFRC). However, whether YAP regulates iron metabolism through other target genes remains uncovered. Here, we observed that system Xc- inhibitor erastin inhibited the binding of WW domain and PSY motif between YAP and transcription factor CP2 (TFCP2), and then suppressed the transcription of ferritin light chain (FTL) mediated by YAP as a co-transcription factor and TFCP2 as a transcription factor. Furthermore, inhibition of FTL abrogated YAP sustain-induced ferroptosis inhibition. Unlike FTH, which exhibited an increase first and then a decrease, FTL transcription continued to decline after the addition of erastin and a decrease in lysine acetyltransferase 5 (KAT5)-dependent acetylation of FTL was also observed. In lung adenocarcinoma (LUAD) tissues, lipid peroxidation and labile iron decreased, while YAP, TFCP2 and FTL increased. The lipid peroxidation marker 4-Hydroxynonenal (4-HNE) was anti-correlated with the level of FTL and the malignant degree of LUAD, but LUAD tissues with low level of 4-HNE showed a higher sensitivity to ferroptosis. In conclusion, this study indicated that suppression of FTL transcription by inhibiting the YAP-TFCP2-KAT5 complex could be another mechanism for elevating ferroptosis sensitivity and inducing cell death, and ferroptotic therapy is more likely to achieve better results in LUAD patients with lower lipid peroxidation degree.